Histology-directed and imaging mass spectrometry: an emerging technology in ectopic calcification - Taverna, Domenico (Bone, 2015)
The present study was designed to demonstrate the potential of an optimized histology directed protein identification combined with imaging mass spectrometry technology to reveal and identify molecules associated to ectopic calcification in human tissue. As a proof of concept, mineralized and non-mineralized areas were compared within the same dermal tissue obtained from a patient affected by Pseudoxanthoma elasticum, a genetic disorder characterized by calcification only at specific sites of soft connective tissues. Data have been technically validated on a contralateral dermal tissue from the same subject and compared with those from control healthy skin. Results demonstrate that this approach 1) significantly reduces the effects generated by techniques that, disrupting tissue organization, blend data from affected and unaffected areas; 2) demonstrates that, abolishing differences due to inter-individual variability, mineralized and non-mineralized areas within the same sample have a specific protein profile and have a different distribution of molecules; 3) avoiding the bias of focusing on already known molecules, reveals a number of proteins that have been never related to the disease nor to the calcification process, thus paving the way for the selection of new molecules to be validated as pathogenic or as potential pharmacological targets.